2016
DOI: 10.3847/0067-0049/225/2/28
|View full text |Cite
|
Sign up to set email alerts
|

Lamost Observations in the Kepler Field. Analysis of the Stellar Parameters Measured With Lasp Based on Low-Resolution Spectra*

Abstract: All of the 14 subfields of the Kepler field have been observed at least once with the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (lamost, Xinglong Observatory, China) during the 2012-2014 observation seasons. There are 88,628 reduced spectra with SNR g (signal-to-noise ratio in g band) ≥ 6 after the first round (2012-2014) of observations for the lamost-Kepler project (LKproject). By adopting the upgraded version of the lamost Stellar Parameter pipeline (lasp), we have determined the atmospheric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 64 publications
(60 reference statements)
3
48
0
Order By: Relevance
“…) will focus on the same topic with a database more than twice the previous spectral library, from 61 226 to 173 971. The number of common stars which have been observed by both Kepler and LAMOST is 76 283, a number larger than twice the data size of Ren et al (2016). In addition, the previous spectra have been re-analyzed with the updated version of the LASP code, v2.9.7, where the determination of uncertainty of radial velocity is improved significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) will focus on the same topic with a database more than twice the previous spectral library, from 61 226 to 173 971. The number of common stars which have been observed by both Kepler and LAMOST is 76 283, a number larger than twice the data size of Ren et al (2016). In addition, the previous spectra have been re-analyzed with the updated version of the LASP code, v2.9.7, where the determination of uncertainty of radial velocity is improved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the previous spectra have been re-analyzed with the updated version of the LASP code, v2.9.7, where the determination of uncertainty of radial velocity is improved significantly. The new calibration examines the reliability of the previous results provided by Ren et al (2016), to establish more generic calibration formulae.…”
Section: Discussionmentioning
confidence: 99%
“…Data 130 Release 3 includes 5.75 million spectra and stellar parameters for >3 million stars. LAMOST has an ideal view of the field observed for four years by the Kepler satellite, and several groups have used the ∼50,000 stars observed in the Kepler field to characterize its stellar populations (e.g., Dong et al 2014;Frasca et al 2016;Ren et al 2016;Chang et al 2017;Dong et al 2017). Other work based on LAMOST spectra includes measurements of stellar activity (e.g., Fang et al 2016) and identification of important subclasses of objects from ultra-metal-poor stars (e.g., and metalliclined Am stars (e.g., Hou et al 2015).…”
Section: Overview Of the Survey Landscapementioning
confidence: 99%
“…Gao et al (2015 found that the standard deviations of 110 K, 0.11 dex and 4.91 km s −1 , for T eff , [Fe/H] and RV. According to the work of Ren et al (2016), LAMOST's T eff and [Fe/H] have the deviation of about 100 K and 0.1 dex in Kepler field, respectively. The pipeline and these independent validations confirm the accuracy of T eff and [Fe/H] for dwarfs, which is matching the coverage of parameters in our sample.…”
Section: Datamentioning
confidence: 99%